(untitled) (Al-Academy, 2026)
This research examines the evolution of sciences and arts throughout human history. Its significance lies in providing references that contribute to and aid in developing sources of inspiration and imagination for the industrial designer. This enables them to present their intellectual, aesthetic, and functional inputs, which contribute to enhancing the potential for induction and the future of the industrial product. This is achieved through scientific material and its translation into the practical reality of design, manifested in functional-kinetic forms imbued with meanings and connotations related to the directions of kinetic art and its applications in industrial design under the Delaunay algorithm.